Patient-Centered Care in Diagnostic Radiology. Issue 1 (January 2015) - Davis, Derik L.; Mulligan, Michael E.; Moszkowicz, Arie; Resnik, Charles S.
<x xml:space="preserve">Abstract</x> Background: Since most radiologists do not meet with patients, questionnaires often substitute for face-to-face interviews to collect patients' history. We report the effect of direct radiologist-patient interviews on the quality of patient history recorded for musculoskeletal magnetic resonance imaging. Methods: Magnetic resonance imaging questionnaires completed by outpatients were separated into 2 cohorts: (1) imaging center (IC) forms with no radiologist interviews; (2) hospital (H) forms with radiologist-patient interviews. Three blinded radiologists independently scored each questionnaire for quality on a 5-point scale. A separate quantitative analysis was also performed. The unpaired t test, Fischer exact test, and χ2 test were used to compare the cohorts. Results: The mean score of the H cohort among reviewers was superior to the IC cohort: 3.79 (±0.98) versus 3.04 (±1.00), P < .0001. Each reviewer also independently found the H cohort to be of higher quality for patient history, P < .0001. For the IC cohort, 7.8% of questionnaires did not report a single symptom versus 0.0% in the H cohort, P = .0331. Also, the IC cohort recorded symptoms in 2 or less words more often than the H cohort, P < .0001. Conclusion: Brief radiologist-patient interviews are superior for obtaining a higher quality of patient history for musculoskeletal MRI than patient questionnaires alone.